Exploring factors associated with healthcare professionals’ subjective perceptions of complex issues in primary care in Japan: a self-administered survey study on confidence, satisfaction and burden levels - Junji Haruta; Ryohei Goto (BMJ Open)
Objective The aim of this study was to explore factors associated with healthcare professionals’ subjective perceptions of complex issues in primary care settings in Japan.Design Cross-sectional survey conducted through a self-administered web-based questionnaire.Setting Japan, from June to October 2020.Participants Healthcare professionals recruited via an email list from the Japan Primary Care Association.Measures The questionnaire assessed subjective perception of satisfaction, confidence and burden regarding complex issues using a 100 mm Visual Analogue Scale (VAS). Explanatory variables included the Japanese version of the Self-assessment Scale of Interprofessional Competency (JASSIC), basic demographic information, administrative experience and an organisational climate scale. This scale comprised the ‘Plan, Do, See’ (PDS) factor for management and the ‘Do’ factor in a leader-centred direction for those working under compulsion. Factors associated with subjective perceptions were analysed using binomial logistic regression analysis and Bonferroni analysis (p<0.017).Results Data from 593 participants (average age of 41.2 years, including 133 nurses, 128 physicians and 120 social workers) were analysed. Median (quartile) VAS scores for satisfaction, confidence and burden were 50 (36–70), 52 (40–70) and 50 (30–66), respectively. Higher satisfaction group was significantly associated with PDS factor, Do factor and JASSIC Score. Greater confidence group associated with older age, male, Do factor, administrative experience and JASSIC Score. No factors were significantly associated with the higher perceived burden.Conclusion These findings reveal that interprofessional competency self-assessment influence perceptions of complex issues among healthcare professionals. Moreover, satisfaction with complex issues might be enhanced by a manageable organisational climate, while confidence might be influenced by personal attributes.